An effective way to measure practical intelligence from a laboratory experience - Zol Bahri, Razali, Dr.; Trevelyan, James P. (Central Queensland University, 2013)
Proceedings of the Research in Engineering Education Symposium (REES) 2009 was organized by Central Queensland University, Australia, 20th - 23rd July 2009 in Palm Cove, Queensland, Australia.